Sejarah Islam di Nusantara Pengaruh Kebudayaan Arab dan Persia Dalam Penyebaran Islam di Nusantara - Anzuli Novela; Alfiani Hapsari; Annisa Maulina; Apap Maftuhah; Kiswah Halimah; Ryan Nur Arifin; Pingkan Sodriatul Amnia; Faiz Fikri Al Fahmi (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
This writing explores how Arab and Persian culture influenced the spread of Islam in the archipelago. Through an accommodative, acculturative and syncretic approach, Islam in Indonesia developed with the strong influence of these two cultures. The main focus of this writing is to look at the role of Arab and Persian culture in the Islamization process through trade routes, diplomatic relations, art, architecture and literature. The method used in this writing is a qualitative method with a literature study approach. Data was collected from various literature discussing the history and development of Islam in the archipelago, especially regarding the influence of Arab and Persian culture. The results show that Arab and Persian culture has a significant role in the spread of Islam in the archipelago. The discovery of the tombs of Persian ancestors from the 14th century AD such as Fatimah bint Maimun and Malik Ibrahim from Kasyan in Java is evidence of this influence. During the Umayyad and Abbasid caliphate, the Persian Empire had close ties with the Islamic world and played an important role in the spread of Islam to the archipelago through trade and diplomatic relations. The influence of Arab and Persian culture not only introduced Islamic teachings to the local population, but also shaped Islamic identity. in the archipelago. Trade and diplomatic relations are the main channels for the spread of Islamic teachings and practices, and it is concluded that Arab and Persian culture has a very important role in the Islamization process in the archipelago. The influence of these two cultures not only spread the religion of Islam, but also enriched and shaped Islamic cultural identity in Indonesia, making Islam an integral part of the lives of the people of the archipelago.